Business ethics in Islam - Qadri, Hussain Mohi-ud-Din (Islamic business and finance series, 2020)
1. Islamic Economy and Its Main Characteristics -- 2. The Key Features of the Islamic Economic System -- 3. Reflections on Licit and Illicit Transactions -- 4. Sharī'ah Rules on Usury (riba) -- 5. Restriction for the Business Class -- 6. Seven Highly Destructive Practices of Traders -- 7. The Legal Status of Contracts -- 8. The Islamic Way of Business and Trade -- 9. Sharia Rules On Giving And Receiving Loans -- 10. Zakāt -- 11. Contemporary Issues in Islamic Business and Trade -- 12. Islamic System of Banking and Finance -- Glossary -- Bibliography -- Index.